2019
DOI: 10.3390/v11121142
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Survey and Phylogenetic Analysis of Atypical Porcine Pestivirus (APPV) Identified in Swine and Wild Boar from Northern Italy

Abstract: Atypical porcine pestivirus (APPV) is a newly recognized member of the Flaviviridae family. This novel porcine pestivirus was first described in 2015 in the USA, where it has been associated with congenital tremor type A-II in new-born piglets. APPV is widely distributed in domestic pigs in Europe and Asia. In this study, a virological survey was performed in Northern Italy to investigate the presence of APPV using molecular methods. Testing of 360 abortion samples from pig herds revealed two APPV strains from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…CT in newborn piglets was first reported in 1922, but the causative agent has always been a mystery. Viral agents responsible for type A-Ⅱ CT had been seeking for decades until APPV was identified in USA and other countries in 2015 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. APPV have been detected in serum, thymus, peripheral lymphoid organs (spleen, tonsil, submaxillary lymph node and inguinal lymph node), nervous system (brain stem, brain, and cerebellum), digestive system (duodenum) and semen [1,8,29,30,31,32], which indicated that this virus has widespread tissue tropism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CT in newborn piglets was first reported in 1922, but the causative agent has always been a mystery. Viral agents responsible for type A-Ⅱ CT had been seeking for decades until APPV was identified in USA and other countries in 2015 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. APPV have been detected in serum, thymus, peripheral lymphoid organs (spleen, tonsil, submaxillary lymph node and inguinal lymph node), nervous system (brain stem, brain, and cerebellum), digestive system (duodenum) and semen [1,8,29,30,31,32], which indicated that this virus has widespread tissue tropism.…”
Section: Discussionmentioning
confidence: 99%
“…sequencing (NGS) from clinical samples in the United States in 2015 [1]. Since then, the presence of APPV in new born piglets with congenital tremor (CT) has been reported in many countries worldwide [2,3], such as USA [4], the Netherlands [5], Germany [6], Austria [7], Spain [8], Brazil [9], Hungary [10], England [11], Canada [12], Sweden [13], China [14], Korea [15], Switzerland [16], Italy [17] and so on, showing that APPV has wide geographical distribution around the world. Two independent studies have been reported that congenital tremor (CT) was reproduced following experimental inoculation with serum or tissue-homogenate-pools containing APPV, demonstrating that APPV could be a very likely causative agent of CT in piglets [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that APPV can be found in semen from commercial boar studs [16], hence, the crucial role of semen in the dissemination of APPV requires further investigation. In addition, recent studies have revealed the presence of APPV in wild boars, suggesting that the wild boars may be a critical virus reservoir for APPV [17][18][19]. Further investigation is required to elucidate the role of wild boars in the epidemiology of APPV.…”
Section: Reverse Genetics System May Be a Promising Platform For Appvmentioning
confidence: 99%
“…It may also disguise the appearance and diagnosis of new and emerging pestivirus infections, and it is therefore paramount that we gain a better understanding of these new entities and refine diagnostic capabilities—both at the clinical and the virological level. In this issue, several articles focus on three of these new pestiviruses and the diseases they may cause in pigs and ruminants: LINDA virus [ 21 ], atypical porcine pestivirus (APPV or Pestivirus K), which by now has been detected in many parts of the world [ 22 , 23 , 24 , 25 ], and Bungowannah virus (Pestivirus F) [ 26 , 27 , 28 ].…”
mentioning
confidence: 99%